Whole‐body senescent cell clearance alleviates age‐related brain inflammation and cognitive impairment in mice. Issue 2 (20th January 2021) - Ogrodnik, Mikolaj; Evans, Shane A.; Fielder, Edward; Victorelli, Stella; Kruger, Patrick; Salmonowicz, Hanna; Weigand, Bettina M.; Patel, Ayush D.; Pirtskhalava, Tamar; Inman, Christine L.; Johnson, Kurt O.; Dickinson, Stephanie L.; et al.
Abstract: Cellular senescence is characterized by an irreversible cell cycle arrest and a pro‐inflammatory senescence‐associated secretory phenotype (SASP), which is a major contributor to aging and age‐related diseases. Clearance of senescent cells has been shown to improve brain function in mouse models of neurodegenerative diseases. However, it is still unknown whether senescent cell clearance alleviates cognitive dysfunction during the aging process. To investigate this, we first conducted single‐nuclei and single‐cell RNA‐seq in the hippocampus from young and aged mice. We observed an age‐dependent increase in p16 Ink4a senescent cells, which was more pronounced in microglia and oligodendrocyte progenitor cells and characterized by a SASP. We then aged INK ‐ ATTAC mice, in which p16 Ink4a ‐positive senescent cells can be genetically eliminated upon treatment with the drug AP20187 and treated them either with AP20187 or with the senolytic cocktail Dasatinib and Quercetin. We observed that both strategies resulted in a decrease in p16 Ink4a exclusively in the microglial population, resulting in reduced microglial activation and reduced expression of SASP factors. Importantly, both approaches significantly improved cognitive function in aged mice. Our data provide proof‐of‐concept for senolytic interventions' being a potential therapeutic avenue for alleviating age‐associated cognitive impairment. Abstract : Senescence is a major contributor to aging and age‐related diseases. However, it is still unknown whether senolytics impact on cognitive function during the aging process. We found that both pharmacogenetic clearance of p16Ink4a senescent cells or treatment with senolytic cocktail Dasatinib and Quercetin, reduced senescent microglia in the hippocampus and improved cognitive function in aged mice.